Less parametric methods in statistics - Weldon, Kenneth Laurence (Metodološki zvezki, 2005)
Despite forty years of revolution in the tools available for statistical analysis, the current academic tradition in statistics is remarkably similar to the pre-computer tradition. This tradition is rooted in parametric modeling, estimation, and testing, and optimal procedures based on these models. The paper argues for a shift in emphasis away from parametric modeling and estimation to graphical summary, from omnibus optimal techniques to those that are more context-specific, and from goals of objectivity to goals of revelation. It is suggested that the emphasis in statistical education should be rebalanced to reflect certain modern computer-based techniques.
Keywords: Statistical methods; Statistične metode; matematična statistika; parametrične metode